Association between central auditory processing mechanism and cardiac autonomic regulation - Regaçone, Simone F. [UNESP]; Lima, Daiane D. B. [UNESP]; Banzato, Mariana S. [UNESP]; Gução, Ana C. B. [UNESP]; Valenti, Vitor Engrácia [UNESP]; Frizzo, Ana Cláudia Figueiredo [UNESP] (My University, 2014)
Background: This study was conducted to describe the association between central auditory processing mechanism and the cardiac autonomic regulation. Methods: It was researched papers on the topic addressed in this study considering the following data bases: Medline, Pubmed, Lilacs, Scopus and Cochrane. The key words were: “auditory stimulation, heart rate, autonomic nervous system and P300”. Results: The findings in the literature demonstrated that auditory stimulation influences the autonomic nervous system and has been used in conjunction with other methods. It is considered a promising step in the investigation of therapeutic procedures for rehabilitation and quality of life of several pathologies. Conclusion: The association between auditory stimulation and the level of the cardiac autonomic nervous system has received significant contributions in relation to musical stimuli.